Culture-Based Character Design as Structured Visual Communication Strategy in Contemporary Popular Media - Shienny Megawati Sutanto; Marina Wardaya (ULTIMART Jurnal Komunikasi Visual, 2026)
The global development of the comic, game, and animation industries has increased the demand for character designs that are not only visually appealing but also possess strong and communicative cultural identities. The problem identified is that local practices of culture-based character design often remain trapped in superficial aesthetic approaches, where cultural elements are used merely as visual ornaments without deep meaning. This research aims to formulate a culture-based character design strategy as a structured visual communication practice, positioning culture as a meaning system translated into visual decisions. The study employs a qualitative approach through theoretical review and in-depth interviews with three professional creators and two design educators active in the creative industry ecosystem. Data were analyzed using thematic analysis to map strategic patterns emerging from character design practices. The results formulate four strategic stages: in-depth cultural research, semiotic translation through a symbol bank, inside-out character construction, and interpretative adaptation to popular media. This research concludes that characters function as communication media bridging local cultural identity with global audiences through consistent sign systems, with the main contribution being a perspective shift from aesthetic activity to cultural interpretation practice. Further research is recommended to test the effectiveness of this strategic framework on audience reception and its broader impact on the creative industry.